Activity-Based Costing Adoption Rates in Tanzanian Manufacturing and Service Sectors: A Comparative Study - Molela, Godfrey Frank; Kasoga, Pendo Shukrani; Ismail, Ismail Juma (Disclosure: Journal of Accounting and Finance, 2024)
The overall objective of this study was to ascertain the difference in ABC adoption rates between the manufacturing and service sectors in Tanzania. Based on the cross-sectional survey design, primary data were collected from 188 companies located in Dar Es Salaam, Arusha and Dodoma regions. The inferential statistics from chi-squared (X2) test results revealed that, p= 0.692 in country-wide was greater than 0.05, hence failed a condition to reject a null hypothesis (H0). It was therefore concluded that, the difference in ABC adoption rates between the Tanzanian manufacturing and service sectors was not statistically significant. This conclusion was consistent in all the three research areas including Dar es Salaam (p= 0.622), Arusha (p= 0.193) and Dodoma (p= 0.986). The results give the implication that, a policy to be developed by a Tanzanian government to address the problem of low rate of 1.1% ABC adoption, should be uniform to both the manufacturing and service sectors. It is also important to note that, the results suggested an equal allocation of resources across both sectors in fostering companies to adopt the system.